Νεοελληνική ρητορεία - Τσάτσος, Κωνσταντίνος Δημ., 1899-1987 (Βασική βιβλιοθήκη / Αετός ;, 1955)
Τρικούπης, Σπυρίδων -- Βαλαωρίτης, Αριστοτέλης -- Ράλλης, Γεώργιος -- Τρικούπης, Χαρίλαος -- Δελιγιάννης, Θεόδωρος -- Βενιζέλος, Ελευθέριος -- Γούναρης, Δημήτριος -- Σοφούλης, Θεμιστοκλής κ.άλ.